ASOSIASI PENYAKIT ALERGI ATOPI DENGAN IgG ANTI HELICOBACTER PYLORI PENELITIAN OBSERVASIONAL KASUS KONTROL ANALITIK DI UNIT RAWAT JALAN PENYAKIT DALAM RSU Dr SOETOMO SURABAYA - PP, Agung; H, Novida; D, Fetarayani; A, Baskoro; G, Soegiarto; C, Effendi (journal of internal medicine, 2012)
Approximately  20%  of  the  world  populations  suffer  from  IgE-mediated  allergic  diseases. Although  genetic  factors play an  important  role  in  the manifestation of allergic disease,  the existence of other  factors  such as  lifestyle  factors, socioeconomic factors and presence of oro-fecal infection including Helicobacter pylori infection also take a part. This is  based  on  the  hygiene  hypothesis  that  infections  in  childhood  can  reduce  allergic  diseases. We  conduct  a  study  to analyze negative association between allergic diseases with IgG anti Helicobacter pylori. This is a matched case control study involved 52 patients in Internal Medicine outpatient ward Dr. Soetomo Hospital Surabaya consisting of 26 patients with allergic diseases as a group of cases and 26 non-allergic patients as controls. Allergic disease was diagnosed by anamnesis, physical examination, and skin prick tests, whereas IgG anti Helicobacter pylori was measured using immune- chromatography  technique. We  found  in  the allergic group  there were 19 patient  (73.08%) with positive Helicobacter pylori and 7 patient (26.92%) with negative result.Whereas in control group there were 21 patient (80.77%) with positive Helicobacter pylori  result and 5 patient  (19.23%) were negative. Helicobacter pylori serology had protective effect  to allergic disease (OR 0.67, CI 95%). Was the conclusion, there is negative association between atopic allergic diseases with IgG anti Helicobacter pylori
Keywords: IgE-mediated, allergic disease, Helicobacter pylori